Post-Electoral Political Exclusion Following the 2024 Simultaneous Regional Elections in West Nusa Tenggara (NTB) - Rifai, Rifai; Haeril, Haeril (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study critically investigates the contours of post-electoral political exclusion in West Nusa Tenggara (NTB) following Indonesia’s 2024 Simultaneous Regional Elections, situating the phenomenon within broader democratic deficits in representation and deliberation. Anchored in the theoretical intersection of elite domination and bureaucratic politicization, the research explores how exclusionary practices are institutionally embedded through strategic civil service reshuffling and symbolic power consolidation by victorious political coalitions. Employing a qualitative, critical case study approach, the study draws on in-depth interviews, participatory observation, and document analysis to construct a nuanced understanding of exclusion mechanisms. Key findings reveal that the electoral triumph of the KIM PLUS coalition catalyzed a reconfiguration of local power alliances, marginalizing opposition actors and transforming bureaucratic appointments into instruments of political reward. The post-election vacuum in over ten strategic governmental roles became an arena for political capitalization, wherein meritocratic procedures were eclipsed by informal networks, loyalty politics, and clientelism. Furthermore, the mutation of educational leadership positions, under the pretext of pedagogical reform, demonstrated the infiltration of partisan logic into ostensibly neutral institutions. These dynamics erode institutional integrity, compromise administrative neutrality, and precipitate a broader crisis of democratic legitimacy. The research concludes that post-electoral exclusion in NTB functions not merely as a residual anomaly of electoral cycles, but as a systemic manifestation of symbolic domination, structurally reproducing elite control while hollowing out spaces for genuine participation. This phenomenon poses a critical threat to democratic resilience and necessitates urgent normative and institutional reforms to safeguard inclusive governance.